Studies and research regarding acclimatization and breeding of new vegetable plant, Momordica charantia at V.R.D.S. Buzău, România - Lagunovschi-Luchian Viorica; Vinatoru Costel; Zamfir Bianca; Bratu Camelia; Tăpăloagă Dana; Radoi Ion (The EuroBiotech Journal, 2017)
Between 1996-2015, at V.R.D.S Buzau were conducted researches regarding the acclimatization, breeding and elaboration of crop technology for a new vegetable species, Momordica charantia (bitter cucumber). There were purchased and studied a large number of genotypes which were assessed for a long period; 4 of those have demonstrated increased adaptability, for which they were retained and multiplied in lineage. In time, by specific cucurbits improvement techniques were obtained 4 genetically stabilized accessions noted as G1, early accessions with large fruits,G2, medium fruit size, G3, medium fruit size and L4 with small crunchy fruits, semi tardy. Of these, L3 was homologated and patented under the name of Rodeo, and the other 3 will be proposed for homologation in the future. The studies demonstrated that this species has well adapted to our pedoclimatic conditions; it can be cultivated both in greenhouses and in open fields, in warmer areas, mentioning that for both crop variants it is recommended a drilling system. The new genotypes support various technological variants and can be ecologically cultivated with remarkable results.